TOPONYMY OF VILLAGE NAMES IN PENGABUAN DISTRICT, TANJUNG JABUNG BARAT DISTRICT: ETHNOLINGUISTIC STUDY - Afria, Rengki; Meilani, Meilan; Safitri, Nadila; Yani, Yuni Apri (International Journal of Multidisciplinary Reseach, 2025)
This research was carried out with the aim of finding out about the origins of the village name and finding out the meaning of the village name. The basic problem that led to this research was knowing the origins and meaning contained in the naming of villages in Pengabuan sub-district. This research is descriptive in nature, where the researcher will describe what happens in the field. And this research uses qualitative methods so that data collection is not so complicated. The results of data analysis contained 13 data, including the use of embodiment aspects and social aspects. In the embodiment aspect, there is a natural environmental background in the form of plants and water settings in each village. In the social aspect, there are legendary stories where people carry out social interactions when carrying out daily activities